A survey of computed tomography dose to operators and patients during radiofrequency ablation - Saidatul Ardeenawatie, Awang; C. A., Azlan; K. H., Ng; B. J. J., Abdullah; Megat Syahirul Amin, Megat Ali (Springer-Verlag Berlin Heidelberg, 2010)
4th Kuala Lumpur International Conference on Biomedical Engineering 2008, 25th – 28th of June 2008 was held at Kuala Lumpur, Malaysia. Link to publisher's homepage at http://ezproxy.unimap.edu.my:2072/home/main.mpx